Incorporation of poly(Itaconic acid) with quaternized thiazole groups on gelatin-based films for antimicrobial-active food packaging - Cottet, Celeste (2021)
Poly(itaconic acid) (PIA) was synthesized via conventional radical polymerization. Then, functionalization of PIA was carried out by an esterification reaction with the heterocyclic groups of 1,3-thiazole and posterior quaternization by N-alkylation reaction with iodomethane. The modifica-tions were confirmed by Fourier transform infrared (FTIR) and proton nuclear magnetic resonance (1 H-NMR), as well as ζ-potential measurements. Their antimicrobial activity was tested against different Gram-negative and Gram-positive bacteria. After characterization, the resulting polymers were incorporated into gelatin with oxidized starch and glycerol as film adjuvants, and dopamine as crosslinking agent, to develop antimicrobial-active films. The addition of quaternized polymers not only improved the mechanical properties of gelatin formulations, but also decreased the solution absorption capacity during the swelling process. However, the incorporation of synthesized polymers increased the deformation at break values and the water vapor permeability of films. The antioxidant capacity of films was confirmed by radical scavenging ability and, additionally, those films exhibited antimicrobial activity. Therefore, these films can be considered as good candidates for active packaging, ensuring a constant concentration of the active compound on the surface of the food, increasing products’ shelf-life and reducing the environmental impact generated by plastics of petrochemical origin.